MAJOR TECHNIQUES OF CLT IN LANGUAGE LEARNING - Babayev Javid (Foundations and Trends in Modern Learning, 2023)
The article analyzes the main effective techniques of language learning of the Communicative Language Teaching method. The study scrutinizes the privileges techniques of the CLT in learning and teaching process while applying them effectively. Some techniques have been illustrated in the article. Besides, it has been noted that the usage of native language while learning the foreign language through this method is avoided. Grammar is not prioritized as other methods. It has been revealed that the integration of language skills is observed while teaching the foreign language through this method.